Development of an e-Coaching Framework to Promote Sleep Hygiene Using Machine Learning - Laflor, Arturo; Vazquez-Briseno, Mabel; Murillo-Munoz, Fernanda (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Computational sciences have gradually allowed scientists to develop novel technological projects to promote a healthy way of life. Most efforts have focus in promoting healthy diets and physical activity. Sleeping is also a crucial activity for humans. Poor sleep quality has adverse effects on health and might lead to physical and mental deterioration. Many computer systems have been used to measure sleep quantity and quality; however, there are few efforts to guide users about aspects that can influence sleeping. Sleep hygiene is a concept that allows controlling sleep-related habits and promoting good sleep quality; unfortunately, modern lifestyles can cause people to adopt wrong habits without being aware of their impact on sleep quality. This work describes a framework developed to guide user’s during the day in order to achieve good sleep quality during sleep time. A set of sleep hygiene factors (SHFs) intended to control hours before going to sleep was defined. The framework identifies personal SHFs using machine learning algorithms; furthermore, a new algorithm was designed to improve results. The framework also includes a mobile persuasive system to encourage users to control personal SHFs.